2011
DOI: 10.1111/j.1600-0404.2011.01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the abrupt switch from solution to modified-release granule formulation of valproate

Abstract: Modified-release granule formulation of VPA may be a reliable alternative to solution for its convenience of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Five sources of strong evidence were identified (Table S1) all of which concluded that sprinkle/granule formulations were well‐accepted by children from 3 months of age . The studies also showed a preference for multiparticulates over oral liquids.…”
Section: Resultsmentioning
confidence: 99%
“…Five sources of strong evidence were identified (Table S1) all of which concluded that sprinkle/granule formulations were well‐accepted by children from 3 months of age . The studies also showed a preference for multiparticulates over oral liquids.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the validity of the ASQ has been investigated in Norwegian samples. Decreased scores found in premature children have been regarded as supporting the construct validity of the Norwegian version of the scales [51]. Further studies are needed to assess the validity of the specific language and attention items included in the MoBa questionnaires, namely with regards to concurrent validity in relation to standardized assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a more accurate way of framing our results would be to interpret them as pertaining to relations between attention problems and presence/absence of language delay. In fact, the ASQ high negative predictive value has supported its use as a screening tool in premature children [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Some other medicines have a narrow therapeutic index and need exact dosing, necessitating higher demands on the dosing flexibility of the formulation. The formulations based on solid platform technology can, in contrast to liquid formulations, be manufactured also in slow-release form, which allows less frequent dosing as for example with valproate modified-release granules [8].…”
Section: Ceylon Medical Journalmentioning
confidence: 99%